Essential Oils and Extracts from Argentinian Northwest Plants as Potential Biofungicides for Olive and Grapevine Pathogens: in vitro Studies - Sayago, María; Ormeño, Ivana; Ajmat, María Teresa; Barbieri, Natalia (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
This work studies the effect of 12 botanical products from Argentinian northwest plants on spores and mycelium of Verticillium dahliae and Phaeoacremonium parasiticum, two pathogens of agronomic importance for the region. The fungi were exposed to essential oils (EOs) or ethanolic extracts (EEs), determining the percentage of germinated spores and mycelial growth. All tested EOs and EEs showed varying degrees of antifungal activity, dependent on plant species, extract type, pathogen, and targeted fungal structures. V. dahliae germination was completely inhibited by Zuccagnia punctata and Clinopodium gilliesii EOs. In experiments with EEs, Z. punctata EE was the most effective in suppressing spore germination of both fungi. The C. gilliesii EE also controlled V. dahliae germination. The EEs of Z. punctata, C. gilliesii and Lippia turbinata were the most active against mycelial growth. These three EEs had a fungistatic effect on P. parasiticum while Z. punctata and L. turbinata EEs showed a fungicidal effect on V. dahliae. The products obtained from Z. punctata, C. gilliesii and L. turbinata have potential as biocontrollers against V. dahliae and P. parasiticum. This is encouraging since no effective treatments are available for the diseases involving these pathogens. Highlights: Antifungal activity of plant-derived products varied depending on plant species, extract type, pathogen, and targeted fungal structures. Ethanolic extracts (EEs) showed higher antifungal activity than Essential oils (EOs). V. dahliae was more sensitive to plant product activity than P. parasiticum. The studied botanical products offer promising eco-friendly alternatives for integrated disease management in regional crops.